The Illusion of Wealth and Its Reversal. (October 2016) - Goldstein, Daniel G.; Hershfield, Hal E.; Benartzi, Shlomo
Research on choice architecture is shaping policy around the world, touching on areas ranging from retirement economics to environmental issues. Recently, researchers and policy makers have begun paying more attention not just to choice architecture but also to information architecture, or the format in which information is presented to people. In this article, the authors investigate information architecture as it applies to consumption in retirement. Specifically, in three experiments, they examine how people react to lump sums versus equivalent streams of monthly income. Their primary question of interest is whether people exhibit more or less sensitivity to changes in retirement wealth expressed as lump sums (e.g., $100, 000) or monthly equivalents (e.g., $500 per month for life). They also test whether people exhibit an "illusion of wealth, " by which lump sums seem more adequate than monthly amounts in certain conditions, as well as the opposite effect, in which lump sums seem less adequate. They conclude by discussing how format-dependent perceptions of wealth can affect policy and consumers' financial decision making.